Mechanochemical preparation of a modified NiAl2O4 structure. (18th October 2022) - Rivas, Maria Elena; Blakiston, Charlotte; Seljamäe-Green, Riho T.; Tran, Trung Dung; Thompsett, David; Day, Stephen; Bilbe, Edward; Fisher, Janet
Abstract : An increase in milling energy results in higher levels of non-crystallinity, surface modification and indications of Ni–Al–O interactions. Evidence of mechanochemical activation is demonstrated with higher quantities of NiAl2 O4 . Abstract : Mechanochemical synthesis routes offer a sustainable, simple method for preparing materials. In this work, NiAl2 O4 was synthesised by a mechanically activated method using a high-energy planetary mill and a calcination step. This study aims to identify the effect of different milling energies on the phases, chemical environments and surface composition of the material. In addition, it explores the thermal impact on the decomposition and structure of the materials. The materials were characterised by X-ray phosphorescence (XPS), solid-state UV-VIS (SS-UV-VIS), X-ray diffraction (XRD), nuclear magnetic resonance (NMR), high-resolution transmission electron microscopy (HR-TEM) and thermal gravimetry differential scanning calorimetry (TGA-DSC). A co-precipitated material is used as a reference along with the ground reagents which were used as a baseline. From this in-depth analysis of the material, a good understanding of the disordered partially inverse spinel structure is provided. This study has found that with calcination temperatures of 750 °C and 900 °C a mixed NiAl2 O4  : NiO phase is produced with a Ni enriched surface. The surface is found to be relatively stable with the increase from 750 °C to 900 °C.